2021
DOI: 10.3389/fpsyg.2020.584360
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Capital as Class Strength and Gendered Educational Choices of Chinese Female Students in the United Kingdom

Abstract: The present qualitative study analyzes how cultural capital, gender, class, and family involvement impact Chinese female students’ aspirations of studying in the United Kingdom. We investigated how these factors facilitate or limit female students’ choice of study destination, as well as choices of subject and program. Data were gathered through participant observation and semi-structured interviews in a British university. A total of 25 young Chinese female students from different subject areas took part in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Pero en el extranjero los estudiantes chinos tienen educación de las hijas. Tal vez esto se deba al ambiente laboral negativo para las mujeres en China que las obliga a buscar una mejor educación y obtener un título universitario (Zhang & Tang, 2021).…”
Section: Discussionunclassified
“…Pero en el extranjero los estudiantes chinos tienen educación de las hijas. Tal vez esto se deba al ambiente laboral negativo para las mujeres en China que las obliga a buscar una mejor educación y obtener un título universitario (Zhang & Tang, 2021).…”
Section: Discussionunclassified
“…In addition, some external factors such as the opinions of parents and friends, family financial situation, and the prestige of the university can also influence students' intent to pursue an MD (Buchmann and Dalton, 2002;Mullen et al, 2003;Berggren, 2006;Zhang and Tang, 2021). Several studies have found that parents' expectations and encouragement have a positive and significant impact on students' intent to pursue an MD (Guerin et al, 2014;To et al, 2014).…”
Section: Influencing Factors For Pursuing An MDmentioning
confidence: 99%
“…Numerous scholars have verified that the socioeconomic status of the family has an impact on individual career development (Fan and Williams, 2010;Aguayo et al, 2011;Flores et al, 2017;Zhang and Tang, 2021). Its influence on behavior and cognition is usually indirect rather than direct.…”
Section: Moderating Effects Of Family Incomementioning
confidence: 99%
“…Cultural capital can be highly instrumental in bridging economic and social capitals to empower women with symbolic capital, particularly in the context of sustainable tourism. Social capital renders itself in such a way that it equips a social actor with the capacity to influence a group or individuals or to position themselves in a social setting (Bourdieu, 1986;Zhang & Tang, 2021). In a pertinent study, Yavuz, Karatas-Ozkan, and Howells (2014) show how the transformation of different forms of capital that social entrepreneurs obtain in the Brazilian context helped them fight racial inequalities and discrimination, which led to a change in institutional regulations and norms in different fields.…”
Section: Theoretical Lensmentioning
confidence: 99%